High nickel deposition at low voltage electroplating process by a combination of anions - Buwono, H. P.; Amrullah, U. S.; Takwim, R. N. A.; Kaavessina, M.; Nasir, N. F. (UTEM, 2021)
This research has been performed to understand the impact of the combination of nickel anions of sulfate (SO4 2- ), and chloride (Cl- ) in the solution towards nickel deposition. The evaluation was performed for the voltage, weight, and efficiency. The electroplating of nickel was performed by chemical cleaning of the specimen surface, nickel deposition in the nickel solution under specific current density, and post-cleaning to remove the residual solution. The nickel solution was consist of sulfate, and chloride anions compared with nickel sulfate solution only. The result showed that the presence of chloride anions in a sulfate solution lowered the voltage, increased the weight of nickel deposition, and increased efficiency compared with the impact on sulfate solution only. The voltage of a solution consisting of chloride and sulfate decreased by more than 30%, compared with sulfate solution only. The weight of nickel deposited on the specimen surface increased clearly. As the number of chloride anions increased, the nickel deposition increased linearly. Interestingly, the highest nickel weight was achieved at a low chloride anion concentration. The heaviest nickel deposited is 0.7 g was achieved under 0.07 A/cm2 and 15 g/l chloride anions. The nickel deposition efficiency in the combination of sulfate and chloride anions is always higher than 80% compared with nickel sulfate solution only.